2014
DOI: 10.1111/1467-9477.12026
|View full text |Cite
|
Sign up to set email alerts
|

Within‐party Allocation of Committee Seats: Evidence from Danish Local Elections

Abstract: This article examines two traditional and four new explanations of committee composition. Using survey data on 541 Danish local politicians' pre-election committee seat preferences and their actual post-election committee seats, it is found that politicians are more likely to have their committee seat preferences fulfilled the less their preferences for the committees' policy domains differ from those of their fellow party members and the more specialised they are within the jurisdiction area of their preferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…On the other hand, being a member of a standing committee has a positive effect on the politicians’ spending preference for the area relevant to the standing committee. Thus, for the three areas that could be linked to a standing committee, we find a clear positive relationship with committee membership, which to some extent may reflect self‐selection based on preferences (Baekgaard ).…”
Section: Resultsmentioning
confidence: 68%
“…On the other hand, being a member of a standing committee has a positive effect on the politicians’ spending preference for the area relevant to the standing committee. Thus, for the three areas that could be linked to a standing committee, we find a clear positive relationship with committee membership, which to some extent may reflect self‐selection based on preferences (Baekgaard ).…”
Section: Resultsmentioning
confidence: 68%
“…Findings from a study on Danish councillors-who also receive low remuneration for their council work-showed that they are also motivated by their institutional positions, and that holding these positions made them less likely to retire voluntarily (Hjelmar et al 2010, 414). Other findings have shown that being assigned a committee or leadership position is an important factor when it comes to the possibility of re-election (Baekgaard 2014;Martin 2014).…”
Section: Theoretical Framework: From Laymen To Professionalmentioning
confidence: 99%
“…They provide deliberative and scrutiny functions, and may revise or even initiate legislation. Allocation of legislators to these committees is of central importance to the distribution of power within a legislature, as some committees are considered more powerful, prestigious, and influential than others (Baekgaard 2014;Heath et al 2005;Munger 1988). Sitting on the "right" committee can enable legislators to advance their policy or career goals (Crisp et al 2009;Frisch and Kelly 2006).…”
Section: Introductionmentioning
confidence: 99%